Biogenesis of secretory immunoglobulin M requires intermediate non‐native disulfide bonds and engagement of the protein disulfide isomerase ERp44. (27th December 2021) - Giannone, Chiara; Chelazzi, Maria Rita; Orsi, Andrea; Anelli, Tiziana; Nguyen, Tuan; Buchner, Johannes; Sitia, Roberto
Abstract: Antibodies of the immunoglobulin M (IgM) class represent the frontline of humoral immune responses. They are secreted as planar polymers in which flanking µ2 L2 "monomeric" subunits are linked by two disulfide bonds, one formed by the penultimate cysteine (C575) in the tailpiece of secretory µ chains (µs tp) and the second by C414 in the Cµ3. The latter bond is not present in membrane IgM. Here, we show that C575 forms a non‐native, intra‐subunit disulfide bond as a key step in the biogenesis of secretory IgM. The abundance of this unexpected intermediate correlates with the onset and extent of polymerization. The rearrangement of the C‐terminal tails into a native quaternary structure is guaranteed by the engagement of protein disulfide isomerase ERp44, which attacks the non‐native C575 bonds. The resulting conformational changes promote polymerization and formation of C414 disulfide linkages. This unusual assembly pathway allows secretory polymers to form without the risk of disturbing the role of membrane IgM as part of the B cell antigen receptor. Synopsis: While membrane IgM are inserted into B‐cell receptors as µ2 L2 "monomers", only IgM polymers are secreted in primary humoral immune responses. This study uncovers an unexpected step in secretory IgM biogenesis. A highly conserved code of hydrophobic aminoacids, a sugar and cysteine 575 in secretory µ chain tailpieces dictate IgM polymerization. IgM polymerization entails formation of a non‐native disulfide bond linking two cysteines 575 within a secretory µ2 L2 subunit. ERp44 attacks the intra‐subunit disulfide and enhances IgM polymerization. The non‐native disulfide bond promotes further inter‐subunit bonding via Cys414. Abstract : An unusual assembly intermediate ensures formation of secretory IgM polymers without jeopardizing the function of membrane‐associated IgM as part of the B‐cell receptor.